Large Dimensional CeO2 Nanoflakes by Microwave‐Assisted Synthesis: Lamellar Nano‐Channels and Surface Oxygen Vacancies Promote Catalytic Activity. Issue 18 (24th July 2018) - Ding, Huihui; Yang, Jingxia; Ma, Shuyi; Yigit, Nevzat; Xu, Jingli; Rupprechter, Günther; Wang, JinJie
Abstract: Large nano‐structured flakes of CeO2 (20–80 nm in thickness, up to 5.6 μm in diameter) were synthesized by a combination of microwave (MW), ultraviolet (UV) and ultrasound (US), with or without pressure (P). The CeO2 structures were systematically examined by XRD, SEM, N2 sorption, HRTEM, XPS, Raman and H2 ‐TPR. The synthesized CeO2 nanoflakes were composed by 3.0–7.5 nm nanoparticles with the (111) surface exposed, and laminated to nanoflakes with 3.42–3.85 nm nano‐channels in between. MW‐assisting was beneficial to form a higher surface Ce 3+ /(Ce 3+ +Ce 4+ ) ratio and surface oxygen vacancies during short synthesis procedure. A Raman peak at 480 cm −1 correlating with bulk Ce 3+ was detected. H2 ‐TPR found MW and MW+P had more surface Ce 3+ (surface oxygen vacancies). CO oxidation and imine conversion proved that MW+P was the optimum condition to produce highly active CeO2 nanoflakes. The much better catalytic performance than CeO2 from solvothermal preparation, due to the larger channel gap (3.85 nm), a higher Ce 3+ /(Ce 3+ +Ce 4+ ) ratio (32 %) and more surface oxygen vacancies on the particles of the organized flake structures. Abstract : CeO promotion : CeO2 nanoflakes obtained by microwave‐assisted synthesis were composed of 5–6 nm nanoparticles, laminated with 3.42–3.85 nm channel gaps. MW‐assisting was beneficial toform a higher surface Ce 3+ /(Ce 3+ +Ce 4+ ) ratio and surface oxygen vacancies during short synthesis procedure. They were profitable to the excellent catalytic performance.